Decolorization of Remazol Briliant Blue R by Laccase from White Rot Fungus Polyporus sp. S133 - Hadibarata, Tony; Tachibana, Sanro (Indonesian Journal of Biotechnology, 2009)
The decolourization of the recalcitrant dye RBBR by the culture filtrate of Polyporus sp. S133 and its isolatedlaccase was investigated. The laccase alone decolorized RBBR. A small molecular weight redox mediator (HBT) wasnecessary to increase the decolorization. The purified laccase totally decolorized the dye of 200 mg l-1 initialconcentration of RBBR when only 1.5 U ml-1 of laccase was used in the reaction mixture. The effects of differentphysicochemical parameters were tested and optimal decolorization rates occurred at pH 5 and at a temperature of 50°C. The effect of surfactants on the decolourization of RBBR was tested with Tween 80, Tween 20, and Brij 35. It wasdemonstrated that Tween 80 was inhibiting substrate for the decolorization while Tween 80 and Brij 35 was noinhibiting effect for the decolorization. Provided that all of the condition is included, it is suggested that laccase maybe suitable for the wastewater treatment of similar anthraquinone dyes.Keywords: Decolorization; Laccase; Remazol Brilliant Blue R (RBBR); Polyporus sp. S133